TALKING THE TALK AND WALKING THE CAREER PATH: ORAL LANGUAGE SKILLS IN TANZANIA - Omondi, Sarah Njeri; Mwangi , Emmanuel Joseph; Shaban, Amina Hassan (Top Linguistic and Language Journal (TLLJ), 2023)
This study explored how English language teachers assess oral language skills in Tanzanian secondary schools. Employing a phenomenological research design, this study used observations, interviews with teachers, and document reviews to investigate classroom practices. The findings indicate that oral language assessment in secondary schools is not comprehensive, and primary assessments are dominated by debates, group discussions, presentations, dialogues, dictation, interviews, questions and answers, and computer-assisted testing. Oral language assessment seemed more beneficial to smaller classes compared to larger classes due to time limitations. The study suggests that students' oral language proficiency could be improved by strengthening both classroom and national assessments. The article also calls for the integration of formative assessment measures to ensure that language proficiency improves among learners. This study establishes that the assessment of oral language skills in Tanzanian secondary schools requires improvement, as end-of-course summative assessments mainly occur without classroom assessments to ensure students' learning progression. Thus, more emphasis needs to be placed on oral language assessment as it is essential for effective communication and job skills